The relation of man and nature in the mainstream of the novel. (Eurasian Journal of Philology Science and Education, 2015)
In this article the novels of the great writers Zhusupbek Aymauytov and Kalikhan Iskakov and the pictures of the nature described there are considered. Aymauytov and Iskakov are known for readers asthe unique masters of the word and true artists who lifted the Kazakh prose to high level. In the article the art and creative and writing skills of Aymauytov Zhusupbek, direct or indirect influence of the descriptionof the nature in the novel on the content, its aim, ideas, composition integrity of the work are analyzed from the scientific point of view. Changes in emotional experiences, moods of the heroes of Zhusupbekmerge with paintings of nature and give beauty to work, and it is considered in detail in comparison with the novels of Kalihan Iskakov.Aymauytov and Iskakov’s art skill in the description of the beautiful nature, fine woods, murmur of the rivers, unique Mountains of Altai, in particular Markakul and Kursha, Buktyrm and Aksu, his own artistictechniques and methods, writing activity are studied. In the research article the parallel description of man and nature in the novel «Akbilek» by Zh. Aymauytov, especially as he begins the description of the nature with a high note and ends it at the same level, without lowering,is estimated as his specific manne. This artistic skill is one of the main traits of thenovel of K. Iskakov «Tuyyk».
Keywords: novel; Kazakh prose; landscape; art style; skill of the writer; relation of the person and nature; author’s approach